(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Kikan Boutique Tabanan is one of the businesses engaged in the trading of fashion products whose business cannot be separated from competitive competition. This study aims to determine the influence of service quality and customer value on customer satisfaction at Kikan Boutique Tabanan. It was conducted at Kikan Boutique Tabanan and the research population was 2,200 customers with a sample of 100 people determined using the slovin formula. The determination of the sample uses nonprability sampling, namely acctidental sampling. Data was collected through observation, interviews, questionnaires, and literature. To test the hypothesis is carried out by classical assumption test, multiple liner analysis, determination analysis, t-test, f-test. The results of the study show that service quality has a positive and partially significant influence on customer satisfaction at Kikan Boutique Tabanan, customer value has a positive and significant influence partially on customer satisfaction at Kikan Boutique Tabanan. Service quality and customer value have a significant simultaneous influence on customer satisfaction at Kikan Boutique Tabanan.